The Gravity of the Grotesque - Tihanov, Galin (2012)
I propose to take the grotesque, both as a discursive genre and a cultural attitude and practice, as a point of departure that allows us to comment more widely on Bakhtin’s Rabelais book and its significance for current debates on subjectivity. In carnival, the epic reverberates in humanity’s boundless memory “of cosmic perturbations in the distant past,” while the novelistic lives in the grotesque fluctuation and removal of distance, and in the irreverent and joyful celebration of resilience through laughter. Like the epic, carnival is about the maintaining of traditional practices, but in an open and charitably insecure, “novelistic” way. The book on Rabelais seems to be the point where, on reconciling and synthesizing culture and life in the acts of the human body, reworking and redrawing the boundaries of cultural taboos, and championing a symbiosis between the epic and the novelistic, Bakhtin sponsors a new sense of tradition inscribed in the irreverent life of folk (community) culture. This celebration of the people re-opens the vexing question about the political implications of Bakhtin’s pronouncements on the epic and the novelistic, on communitarian and individual culture, and on their desired synthesis. But it also enables us to locate Bakhtin’s style of thinking and his specific brand of decentred, indeed dislocated, humanism.